Geochemical partitioning and pollution assessment of Ni and V as indicator of oil pollution in surface sediments from Shadegan wildlife refuge, Iran. Issue 1 (15th October 2016) - Chaharlang, Behnam Heidari; Bakhtiari, Alireza Riyahi; Mohammadi, Jahangard; Farshchi, Parvin
Abstract: The total concentrations and chemical partitioning of Ni, V and Fe have been assessed in surface sediments from 160 sites along the Shadegan wildlife refuge. The results showed that the average total level of Ni, V and Fe in surface sediments were 45.08 ± 12.09, 25.25 ± 20.8 and 25, 979.01 ± 6917.91 μg/g dw, respectively. On the average, the chemical speciation of Ni, V and Fe in most stations were in the order of residual > oxidisable-organic > acid-reducible > exchangeable. In all fractions, the residual was accounted the highest proportion for the metals analyzed. Among the non-residual phases, the proportion of heavy metals in organic matter fraction was higher than other phases collected from all locations. The comparison between measured values in this study and some fresh water sediment quality guidelines indicated that the levels of nickel would be expected to sporadically cause harmful biological impacts on biota in the Shadegan wildlife refuge. Highlights: This survey looks natural and man-made inputs of Ni and V in the Shadegan wetland. Of the all fractions, the residual was found the highest proportion for the metals. Among the non-residual fractions, organic fraction was higher than other phases. Our results show Ni has a lower potential for mobilization of the sediment than V. Compared with some SQGS, the levels of Ni can pose a potential risk to biota.